A novel HLA‐B allele, HLA‐B*15:399, identified in a Chinese individual. (26th September 2016) - Yu, H.; Ji, X.; Liu, Z.; Wang, J.; Chen, Q.
Abstract : One nucleotide replacement in codon 41 of HLA‐B*15:02:01 results in a novel allele, HLA‐B*15:399 .